The revised Bristol Rheumatoid Arthritis Fatigue measures and the Rheumatoid Arthritis Impact of Disease scale: validation in six countries. (26th October 2017) - Hewlett, Sarah; Kirwan, John; Bode, Christina; Cramp, Fiona; Carmona, Loreto; Dures, Emma; Englbrecht, Matthias; Fransen, Jaap; Greenwood, Rosemary; Hagel, Sofia; van de Laar, Maart; Molto, Anna; et al.
Abstract: Objective: To evaluate the Bristol Rheumatoid Arthritis Fatigue Multidimensional Questionnaire (BRAF-MDQ), the revised Bristol Rheumatoid Arthritis Numerical Rating Scales (BRAF-NRS V2) and the Rheumatoid Arthritis Impact of Disease (RAID) scale in six countries. Methods: We surveyed RA patients in France, Germany, The Netherlands, Spain, Sweden and the UK, including the HAQ, 36-item Short Form Health Survey (SF-36) and potential revisions of the BRAF-NRS coping and Spanish RAID coping items. Factor structure and internal consistency were examined by factor analysis and Cronbach's α and construct validity by Spearman's correlation. Results: A total of 1276 patients participated (76% female, 25% with a disease duration <5 years, median HAQ 1.0). The original BRAF-MDQ four-factor structure and RAID single-factor structure were confirmed in every country with ⩾66% of variation in items explained by each factor and all item factor loadings of 0.71–0.98. Internal consistency for the BRAF-MDQ total and subscales was a Cronbach's α of 0.75–0.96 and for RAID, 0.93–0.96. Fatigue construct validity was shown for the BRAF-MDQ and BRAF-NRS severity and effect scales, correlated internally with SF-36 vitality and with RAID fatigue ( r = 0.63–0.93). Broader construct validity for the BRAFs and RAID was shown by correlation with each other, HAQ and SF-36 domains ( r = 0.46–0.82), with similar patterns in individual countries. The revised BRAF-NRS V2 Coping item had stronger validity than the original in all analyses. The revised Spanish RAID coping item performed as well as the original. Conclusion: Across six European countries, the BRAF-MDQ identifies the same four aspects of fatigue, and along with the RAID, shows strong factor structure and internal consistency and moderate–good construct validity. The revised BRAF-NRS V2 shows improved construct validity and replaces the original.